2017
DOI: 10.1038/nn.4612
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus directly infects peripheral neurons and induces cell death

Abstract: Zika virus (ZIKV)-infection is associated with neurological disorders of both the central and peripheral nervous systems (PNS), yet few studies have directly examined PNS-infection. Here we show that intraperitoneally or intraventricularly-injected ZIKV in the mouse could infect and impact peripheral neurons in vivo. Moreover, ZIKV productively infects stem cell-derived human neural crest cells and peripheral neurons in vitro, leading to increased cell death, transcriptional dysregulation and cell-type specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 31 publications
5
70
0
2
Order By: Relevance
“…Other host proteins interacting with ZIKV sfRNA which has role embryonic development are SCML2, TBX2, PROX1, RTF1, ELAVL1, ATF6, SETDB2, PUM3 and ZBTB16. Further, ZIKV affect the differentiation, proliferation and death of neuronal cells (20)(21)(22)(23)(24). This study, provided indication proteins has role in the ZIKV pathogenesis in neuronal differentiation; proliferation and death are TCF4, TCF3, POU6F2, TCF12, FOXO3, REB3L2 and MEF2D.…”
Section: Discussionmentioning
confidence: 64%
“…Other host proteins interacting with ZIKV sfRNA which has role embryonic development are SCML2, TBX2, PROX1, RTF1, ELAVL1, ATF6, SETDB2, PUM3 and ZBTB16. Further, ZIKV affect the differentiation, proliferation and death of neuronal cells (20)(21)(22)(23)(24). This study, provided indication proteins has role in the ZIKV pathogenesis in neuronal differentiation; proliferation and death are TCF4, TCF3, POU6F2, TCF12, FOXO3, REB3L2 and MEF2D.…”
Section: Discussionmentioning
confidence: 64%
“…During infection, viruses hijack the inward transport machinery of the cell [42][43][44][45]. While some viruses are able to fuse with the cell membrane and initiate infection almost immediately after entry, others need to be ferried long distances, e.g., during infection of neural cells [46][47][48][49]. This study focused on events that occur after the initial interaction between ZIKV and its cellular receptor.…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV has been shown to replicate and cross the endothelial barrier without significantly affect its permeability (14, 15). Additionally, it was demonstrated that ZIKV replicates in human peripheral neurons in vitro (16). Thus, replication in motors and sensory tissues, in addition to contributes to viral load, could be a route used by ZIKV to access the peripheral nerves and reaches by retrograde axonal-transport some immuno privileged sites such as the brain (17).…”
Section: Introductionmentioning
confidence: 99%